Retina and glaucoma - American Academy of Ophthalmology (San Francisco : American Academy of Ophthalmology, 1997)
Provision interactive realistically simulates six-patients-physician encounters within the subspecialities of retina and glaucoma.
This cd-rom is available at Multimedia Lab, Perpustakaan Perubatan.
Keywords: Glaucoma; Retina